Heterotopia and the city : public space in a postcivil society - Dehaene, Michiel; De Cauter, Lieven (London : Routledge, 2008)
Heterotopia in a postcivil society / Michiel Dehaene and Lieven de Cauter ##Of other spaces (1967) / Michel Foucault ##Heterotopia : an ecology / James D. Faubion ##Heterotopia : anamnesis of a medical term / Heidi Sohn ##The many mirrors of Foucault and their architectural reflections / M. Christine Boyer ##Heterotopias of difference / Marco Cenzatti ##The space of play : towards a general theory of heterotopia / Lieven de Cauter and Michiel Dehaene ##Heterotopia of the theme park street / Kathleen Kern ##Between shopping malls and agoras : a French history of 'protected public space' / Clément Orillard ##'A kind of instinct' : the cinematic mall as heterotopia / Douglas Muzzio and Jessica Muzzio-Rentas ##The gated community as heterotopia / Setha Low ##A master-planned community as heterotopia : The Villages, Florida / Hugh Bartling ##The 'institutionalization' of heterotopias in Singapore / Xavier Guillot ##Public-space heterotopias : heterotopias of masculinity along the Tel Aviv shoreline / Yael Allweil and Rachel Kallus ##' ... those marvellous empty zones on the edge of our cities ' : heterotopia and the 'dead zone' / Gil Doron ##Stalker unbounded : urban activism and the terrain vague as heterotopia by default / Peter Lang ##'Rubbing the magic lamp' : heterotopian strategies in London's eastern city fringe / Maureen Heyns ##Flow urbanism : the heterotopia of flows / Lee Stickells ##Heterotopias of illusion : from Beauborg to Bilbao and beyond / D. Grahame Shane ##The heterotopian divide in Jakarta : constructing discourse, constructing space / Robert Cowherd ##Dubai offshore urbanism / Alessandro Petti ##'Dead society' in a 'cemetery city' : the transformation of burial rites in Kinshasa / Filip de Boeck ##Heterotopia unfolded? / Hilde Heynen.
boek